Principal's Policy for Minimizing Bullying at Muhammadiyah 2 Ngawi Junior High School - Desi Dwi Maheningsih; Sutrisno Sutrisno (MANAZHIM, 2023)
This study aims to find the causes of bullying, the principal's policy for minimizing bullying, the types of bullying, and the consequences of bullying at SMP Muhammadiyah 2 Ngawi. research method using descriptive qualitative research method. The research subjects were school principals, homeroom teachers for grades VIII and IX, and counseling teachers and students in grades VIII and IX at SMP Muhammadiyah 2 Ngawi. data collection methods used are interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. The results showed that the cause of bullying was peer factors. Types of bullying at SMP Muhammadiyah 2 Ngawi are verbal bullying, physical bullying, even if only occasionally, and extortion or bullying at school, ranging from Rp. 500 – Rp Rp. 1,000 and in the form of snacks. The impact of bullying at SMP Muhammadiyah 2 Ngawi is that the victim feels embarrassed, often cries in class, and becomes a quieter child. Meanwhile, the perpetrators were given points for violations and ordered to clean the classrooms, bathrooms, and mosques. If the perpetrator continues to bully again, the parents will be summoned to school, but so far there has never been a summons from a student's guardian to school because of bullying. The school principal's policy in minimizing bullying at Muhammadiyah 2 Ngawi Middle School is in the form of: (1) making a Decree (SK) on "Manners and Orders of School Social Life for Students", (2) making media posters, (3) working with the police to socialize about bullying, (4) giving lectures after Duha prayers and giving direct advice to students before learning, (5) emphasizing the teachers of SMP Muhammadiyah 2 Ngawi to approach and provide good examples to their students.